Five Eyes indopasifisella alueella tiedustelun kansainvälisen yhteistyön näkökulmasta - Salmi, Teemu (2025)
International intelligence cooperation has existed as long as state-based intelligence itself. In recent decades, an expanded concept of security and the rise of transnational threats have further emphasized its significance. Such cooperation may cover the entire intelligence cycle and include not only information sharing but also joint analysis, training, and coordinated operations. One of the most prominent multilateral intelligence alliances is the Five Eyes, comprising the United States, the United Kingdom, Canada, Australia and New Zealand. The depth and breadth of cooperation within the alliance are unparalleled globally. The aim of this study was to examine how the activities of the Five Eyes collective in the Indo-Pacific region reflect the theoretical framework of international intelligence cooperation in practice. In addition, the study sought to describe the forms of practical intelligence cooperation within the alliance and to assess whether any changes occurred in these practices during the period between 2015 and 2024. The study was conducted as an integrative literature review, analyzing systematically collected academic material. The findings were interpreted using a theoretical framework on international intelligence cooperation. The results indicate that Five Eyes exemplifies the theoretical characteris-tics of multilateral intelligence cooperation. Its activities in the Indo-Pacific re-flect high levels of both depth and scope, driven particularly by China's growing regional influence, transnational threats, and technological developments. Cooperation manifests through shared analysis, operational coordination, liai-son officer activity, and joint training. However, the study was unable to con-clusively identify clear changes in the nature of the cooperation between 2015 and 2024, although certain themes were found to be more prominent during different phases of the examined period.